2004
DOI: 10.1023/b:biop.0000047157.49910.69
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl and Mycorrhizal Fungi on Antioxidative Enzymes in Soybean

Abstract: The effects of different concentrations of NaCl on the activities of antioxidative enzymes in the shoots and roots of soybean (Glycine max [L.] Merr cv. Pershing) inoculated or not with an arbuscular mycorrhizal fungus, Glomus etunicatum Becker & Gerdemann, were studied. Furthermore, the effect of salt acclimated mycorrhizal fungi on the antioxidative enzymes in soybean plants grown under salt stress (100 mM NaCl) was investigated. Activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 30 publications
8
35
0
Order By: Relevance
“…The present study clearly showed that SOD activity was largely induced by G. mosseae but not G. versiforme under salt or saltless conditions, and AMF infection significantly increased the CAT activity of the citrus leaves under salt stress (Figure 3). The results are similar in part to the results obtained by Ghorbanli et al (2004) and He et al (2007), who reported greater SOD activity of salt-stressed soybean inoculated with G. etunicatum or tomato inoculated with G. mosseae. However, several studies suggested that AM symbiosis did not affect CAT activity of salt- The same letter within each column indicates no significant difference among treatments (P < 0.05) NaCl (mmol) Figure 3.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The present study clearly showed that SOD activity was largely induced by G. mosseae but not G. versiforme under salt or saltless conditions, and AMF infection significantly increased the CAT activity of the citrus leaves under salt stress (Figure 3). The results are similar in part to the results obtained by Ghorbanli et al (2004) and He et al (2007), who reported greater SOD activity of salt-stressed soybean inoculated with G. etunicatum or tomato inoculated with G. mosseae. However, several studies suggested that AM symbiosis did not affect CAT activity of salt- The same letter within each column indicates no significant difference among treatments (P < 0.05) NaCl (mmol) Figure 3.…”
Section: Resultssupporting
confidence: 91%
“…A potted experiment showed that SOD and POD activities in roots of tomato colonized by Glomus mosseae were significantly higher than either the non-AM plants under salinity or control conditions (He et al 2007). Ghorbanli et al (2004) reported the enhanced activities of SOD, POD and ascorbate-peroxidase in mycorrhizal soybean plants under salt stress.…”
mentioning
confidence: 99%
“…mediating quick scavenging of ROS so that metabolic processes are least affected. Increased activities of antioxidant enzymes in AMF plants support the findings of Ghorbanli et al (2004) and Abdel Latef and Chaoxing (2011) for tomato. In tomato, Qun et al (2007) reported that salinity-stressed AMF-inoculated seedlings maintained higher activities of SOD, CAT and POD as compared to salt-stressed uninoculated seedlings.…”
Section: Discussionsupporting
confidence: 82%
“…Similar results have been observed by Tang et al (2009) in maize. AMF-induced increase in CAT activity has been reported in soybean (Ghorbanli et al 2004). GR is among active and important components of ascorbateglutathione pathway where the net electron flow is from NADPH to H 2 O 2 resulting in conversion of H 2 O 2 into water (Mittler 2002).…”
Section: Discussionmentioning
confidence: 98%
“…For example, soybean plants inoculated with arbuscular mycorrhizal (AM) fungi showed reduced MDA content and increased APX activity to the oxidative stress generated by paraquat (PQ) [52]. In another study, activities of SOD and peroxidase were increased in the shoots of soybean plants with mycorrhizal (M) fungi grown under NaCl salinity [53]. Once again, a more integrated view is needed and deserves attention.…”
Section: Plant Stressmentioning
confidence: 99%